2014
DOI: 10.1002/poc.3278
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the formation of N‐chloro compounds using N‐chlorosuccinimide

Abstract: b Second-order rate constants were determined for the chlorination reaction of 2,2,2-trifluoethylamine and benzylamine with N-chlorosuccinimide at 25°C and an ionic strength of 0.5 M. These reactions were found to be of first order in both reagents. According to the experimental results, a mechanism reaction was proposed in which a chlorine atom is transferred between both nitrogenous compounds. Kinetics studies demonstrate that the hydrolysis process of the chlorinating agent does not interfere in the chlorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…In the present work, the rate constants obtained for the reactions of OXA with HOCl and t BuOCl were similar and higher than the rate constants obtained in the reaction with NCS. These values follow the same trend as those found with other nitrogenous compounds HOCl0.25emtBuOCl0.25em>0.25emnormalNnormalCnormalS …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present work, the rate constants obtained for the reactions of OXA with HOCl and t BuOCl were similar and higher than the rate constants obtained in the reaction with NCS. These values follow the same trend as those found with other nitrogenous compounds HOCl0.25emtBuOCl0.25em>0.25emnormalNnormalCnormalS …”
Section: Discussionsupporting
confidence: 88%
“…The values for the activation energy obtained in this work were compared with others obtained under similar conditions, which were found in the literature. It was found that they are of the same order of magnitude as those obtained for the reaction of this nitrogenous compound with its analogous N ‐brominating agent (NBS), and with those obtained for the N ‐chlorination reaction of the nitrogenous compound with these chlorinating agents (HOCl, t BuOCl, and NCS) …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, these relationships could also be used to predict the behavior of other nitrogenous compound similar. Also, the effectiveness of the different N ‐chlorinating agents is interesting to compare because of the great importance of these N ‐chlorination reactions in environmental and biochemical processes …”
Section: Introductionsupporting
confidence: 90%